Android programming - Hellman, Erik (Wiley, 2014)
Fine-tuning your development environment -- Efficient Java code for Android -- Components, manifests, and resources -- Android user experience and interface design -- Android user interface operations -- Services and background tasks -- Android IPC -- Mastering BroadcastReceivers and configuration changes -- Data storage and serialization techniques -- Writing automated tests -- Advanced audio, video, and camera applications -- Secure Android applications -- Maps, location, and activity APIs -- Native code and JNI -- The hidden Android APIs -- Hacking the Android platform -- Networking, web service, and remote APIs -- Communicating with remote devices -- Google Play services -- Distributing applications on Google Play store.; Includes bibliographical references and index